Intergenerational Wealth Mobility and the Role of Inheritance: Evidence from Multiple Generations - Adrian Adermon; Mikael Lindahl; Daniel Waldenström (Institute for the Study of Labor (IZA), 2016)
This study estimates intergenerational correlations in mid-life wealth across three generations, and a young fourth generation, and examines how much of the parent-child association that can be explained by inheritances. Using a Swedish data set we find parent-child rank correlations of 0.3–0.4 and grandparents-grandchild rank correlations of 0.1–0.2. Conditional on parents' wealth, grandparents' wealth is weakly positively associated with grandchild's wealth and the parent-child correlation is basically unchanged if we control for grandparents' wealth. Bequests and gifts strikingly account for at least 50 per cent of the parent-child wealth correlation while earnings and education are only able to explain 25 per cent.
Keywords: D31; J62; 330; multigenerational mobility; bequests; mid-life wealth